Association of cognition with functional trajectories in patients admitted to geriatric wards: A retrospective observational study. Issue 10 (16th September 2016) - Hartley, Peter; Alexander, Kerry; Adamson, Jennifer; Cunningham, Carol; Embleton, Georgina; Romero‐Ortuno, Roman
Abstract : Aim: Impaired cognition is common among older patients admitted to acute hospitals, but its association with functional trajectories has not been well studied. Methods: A retrospective observational study was carried out in an English tertiary university hospital. We analyzed all first episodes of county residents aged ≥75 years admitted to the Department of Medicine for the Elderly wards between December 2014 and May 2015. A history of dementia or a cognitive concern in the absence of a known diagnosis of dementia were recorded on admission. A cognitive concern included possible undiagnosed dementia or delirium. Function was retrospectively measured with the modified Rankin Scale at preadmission baseline, admission and discharge. Results: There were 663 first hospital episodes over the period, of which 590 patients survived. Among the latter, 244 had no cognitive impairment, 134 a diagnosis of dementia, 66 a cognitive concern in the absence of a known dementia and 146 had missing cognitive data. When frailty, acuity, age and comorbidity were controlled for, people with known dementia had a similar functional recovery compared with those with no cognitive impairment. People with a cognitive concern, but no known dementia, had lesser functional recovery and greater disability at discharge than those with no cognitive impairment (mean discharge modified Rankin Scale 3.4 compared with 3.1, P  = 0.011). Conclusions: Dementia per se might not be a marker of poor rehabilitation potential. Older people with acute cognitive concerns might be more vulnerable to poor functional recovery. Our cognitive variables are not gold standard, and further research is required to clarify this relationship.Geriatr Gerontol Int 2017; 17: 1438–1443.